METODOLOGI FIKIH KEINDONESIAAN - Ramadhan, M. Rizki Syahrul; Arifin, Syamsul; Huda, Miftahul (IAIN Tulungagung, 2021)
This paper aims to formulate a methodological pattern for Indonesian fiqh, which is a method for developing Indonesian Islamic law and giving an appreciation of Indonesian traditions. It is important to formulate this pattern in order to establish a methodological direction or starting point in establishing effective Islamic law in Indonesia and accordance with the socio-cultural conditions of the community. Several previous studies have contributed in establishing this methodological direction, but are not yet comprehensive. Through the study of comparative texts that analyzed using an Islamic legal philosophy approach to the thoughts of Hasbi Ash-Shiddieqy, Hazairin, and Abdurrahman Wahid, this paper concludes that the Indonesian fiqh methodology departs from the spirit to utilize fiqh so that it can be applied in Indonesian society mediated by local customs. To utilize the fiqh, the technical methodologies are various, but the pattern based on the fiqh methodology has a few things in common, that are utilizing